THE EFFECT OF PRICE ON CONSUMER SATISFACTION OF DIM SUM CEMAL CEMIL IN MEDAN CITY - Ade Rahma Ayu; Aqila Zulaikha Majid; Regina Aulia Natasya; Vira Adelia Syafitri; Nabila Dwi Agustin; Rizki Al Akbar; Christian Parulian Manurung (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of price on customer satisfaction at Dim Sum Cemal Cemil in Medan. The study employed a quantitative approach using a survey method, in which questionnaires were distributed to 60 respondents who were customers of Dim Sum Cemal Cemil. Accidental sampling was used as the sampling technique. The data were analyzed using IBM SPSS Statistics software through validity tests, reliability tests, normality tests, heteroscedasticity tests, simple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results showed that all statement items were valid and reliable. The results of the simple linear regression analysis yielded the equation Y = 11.892 + 0.694X, indicating that price has a positive effect on customer satisfaction. The t-test results showed a calculated t-value of 6.536 with a significance level of 0.000 (<0.05), thus proving that price has a positive and significant effect on customer satisfaction. The F-test results also showed a significance value of 0.000, meaning the regression model is appropriate for use. Furthermore, the coefficient of determination (R-squared) of 0.424 indicates that price explains 42.4% of the variation in consumer satisfaction, while the remaining 57.6% is influenced by other factors not examined in this study. Thus, it can be concluded that price is one of the key factors influencing customer satisfaction at Dim Sum Cemal Cemil in Medan. Therefore, the business is advised to maintain a pricing policy that aligns with product quality and customer purchasing power in orders to enhance customer satisfaction and loyalty.